Analysis UX Design e-Commerce "Key Kaos" with Lean UX - Dwi Prasetyo, Edi; Khoir Alhaq , Ahmad (Information Technology International Journal, 2024)
This research explores the evaluation of User Experience (UX) design at the Key Kaos online store using the Lean UX approach. Key Kaos online store required user-centered design to increase customer satisfaction and drive engagement. This study integrates Lean UX principles to simplify the design process, encourage collaboration, and rapid iteration.The research methodology includes a combination of user feedback, usability testing, and iterative prototyping, which aligns with the Lean UX framework. Through this iterative process, this research aims to identify key weak points and areas of improvementin the existing UX design of the Key Kaos online store. These findings are expected to provide valuable insights in increasing user satisfaction, improving usability, and optimizing the overall user journey in the market.Additionally, this research explores the impact of Lean UX on cross-functional collaboration, aiming to identify how Lean UX facilitates communication and collaboration between designers, developers and other stakeholders. By assessing the effectiveness ofLean UX in the context of Key Kaos, this research contributes to a broader understanding of its application in the market environment.The expected outcomes of this research include actionable recommendations to improve the UX design of Key Kaos online stores, ultimately contributing to market success by creating a more user-friendly and efficient platform. Additionally, research insightsregarding the application of Lean UX principles can inform future efforts in marketplace UX design, offering a valuable reference for designers and researchers looking to optimize user experiences in online marketplaces.